Using reading while listening in English as a foreign language (EFL) learning context - Asrimawati, Inayati Fitriyah; Margana, Margana (JEES (Journal of English Educators Society), 2020)
The benefits of reading while listening for English as a Foreign Language (EFL) learners have been investigated in different EFL learning contexts. Some studies found that simultaneous reading while listening promotes positive impacts on students’ reading and listening skills. It also helps L2 learners’ fluency and comprehension of reading and listening. Moreover, it can assist L2 learners in acquiring new language input in a new learning environment. Hence, this article reviews some research papers related to the implementation of reading while listening (RWL) program in EFL learning context. Furthermore, to answer the research questions: 1) What is reading while listening?; 2) What are the effects of using reading while listening for EFL learners? How to apply the reading while listening program within the EFL classroom? To answer these questions, this article examines the use of RWL for EFL learners based on the research methodology, subject, instrument used, result and suggestion, including the principles of implementing simultaneous reading and listening within the EFL classroom. HIGHLISGHTS Highlights Reading While Listening (RWL)simultaneously can support students with low reading or listening fluency rate. Simultaneous reading while listening affects students reading and listening skills for a long period of time. A guideline of RWL program implementation based on ER/EL principles is discussed thoroughly.